Effect of Genotype and Growth Temperature on Sorghum Grain Physical Characteristics, Polyphenol Content, and Antioxidant Activity. Issue 4 (22nd March 2016) - Wu, Gangcheng; Johnson, Stuart K.; Bornman, Janet F.; Bennett, Sarita; Singh, Vijaya; Fang, Zhongxiang
Abstract : This paper reports how genotype and growth temperature affect the physical characteristics and polyphenol content in sorghum grains. Two day/night temperature regimes, 32/21 and 38/21°C, were used to grow six sorghum genotypes (CCH1, CCH2, AQL33/QL36, Ai4, PI563516, and IS 8525). The physical characteristics (hardness, weight, and diameter) of sorghum grain and their free, bound, and total polyphenol contents were determined. Grain antioxidant activity was evaluated by 2, 2′‐azinobis(3‐ethylbenzothiazoline‐6‐sulfonic acid) diammonium salt and 2‐2‐diphenyl‐1‐picrylhydrazyl assays. The results indicate that the weight and diameter of the sorghum kernels were significantly increased in all genotypes except for CCH1, under higher temperature, whereas kernel hardness decreased. Genotype had a significant influence polyphenol content (IS 8525 about four times higher than PI563516 under optimum temperature) and antioxidant activity, but temperature did not, with the exception of IS 8525 in which polyphenol content (reduced by about 10%) and antioxidant activity were lower at the high temperature. Polyphenol content was strongly positively correlated with antioxidant activity. This research provides valuable information on the properties of different sorghum genotypes under expected future increased temperatures that may be of value for varietal selection for specific end use.